2021
DOI: 10.32598/biomechanics.6.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Course of Up-cholugi and Yup-chagi Exercises on the Kinematic Indices of the Knee and the Incidence of Bow-leggedness (Genu Varum) in Professional Taekwondo Practitioners

Abstract: Objective: Knee brace is one of the lower limb abnormalities. This study aimed to investigate the effect of knee kinematical parameters on the development of knee Genu Varum. Methods: This study’s statistical sample was 32 taekwondo practitioners with red and black belts of sports clubs in the northeast of Tehran, determined using G-Power software and in two groups of 16 people in terms of gender, age, and membership in the field. The 8-week training intervention, which included 3session of 1-hour training ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This is the guarantee of winning the game. 11 Conscious effort, tenacious struggle, strict self-discipline, the courage to challenge difficulties, and other willpower qualities play a crucial role in the final victory of volleyball players. Competition is a need.…”
Section: Discussionmentioning
confidence: 99%
“…This is the guarantee of winning the game. 11 Conscious effort, tenacious struggle, strict self-discipline, the courage to challenge difficulties, and other willpower qualities play a crucial role in the final victory of volleyball players. Competition is a need.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic analysis has shown that the speed of the distal segment depends on the speed of the proximal segment and the interaction between each segment [ 8 ]. Kicking at high speeds has a positive effect on scoring and continuous skills, but it also increases soft tissue tension due to repeated momentary muscle contractions [ 9 ]. Increased tension in soft tissues can lead to musculoskeletal stress, damage to surrounding soft tissues, and misalignment.…”
Section: Introductionmentioning
confidence: 99%